The Influence Of Taxpayer Awareness And Administrative Sanctions On Restaurant Taxpayer Compliance - Fahrul Alam Masruri; Iis Iis Istikomah (SINTESA, 2022)
This research is motivated by the disobedience of restaurant taxpayers in paying their tax obligations based on the amount of restaurant tax arrears in 2017-2021. This study aims to determine how much influence Taxpayer Awareness and Administrative Sanctions have on Taxpayer Compliance. The research method used by the researcher is a survey method with a quantitative approach. Data were collected using a disproportionate stratified random sampling technique by distributing questionnaires to 99 restaurant taxpayers as samples. The data analysis techniques used in this study are normality test, multiple linear regression analysis, product moment correlation, coefficient of determination test, hypothesis testing t-test and F-test using the IBM SPSS Version 25 program. The results of this study indicate that: (1) Taxpayer awareness has a positive and significant effect on Restaurant Taxpayer Compliance, with a regression coefficient value of 0.776, a value of tcount> ttable (5.521>1.985) with a significant value of 0.000<0.05. (2) Administrative Sanctions have a positive and significant effect on Restaurant Taxpayer Compliance, with a regression coefficient value of 0.225, a value of tcount>ttable (2.752>1.985) with a significant value of 0.007<0.05. (3) Taxpayer Awareness and Administrative Sanctions have a positive and significant effect on Restaurant Taxpayer Compliance, with a value of Fcount>Ftable (29.306>3.09), with a significant value of 0.000<0.05.